La evaluación pedagógica y su incidencia en el desarrollo competitivo en las pruebas de medio fondo en los atletas pre-juveniles de la Federación Deportiva de Loja periodo 2013 - Narváez Galván, Edwin Fabián (2014)
This research work has been titled. The educational assessment and its impact on the competitive development in middle-tests on pre-junior athletes of the Sports Federation of Loja 2013 period. Speaking of educational assessment to mean a medium used to check the teaching learning to take into account this type of evaluation have to be applied according the degree of efficiency in the competitive development in middle-tests to avoid failure in the competitive athlete development that allows a raise issues of sports training . athlete that should render Likewise we can talk about how the pedagogical problem affects monitoring in preparation for the competitive development of the category Pre lojanos athletes - youth during the period 2013? In addition to formulate the following general objective, identify the level of impact of pedagogical control in the competitive development of middle-tests of pre-junior athletes of the Sports Federation of Loja. The methodology used in this research work was raised on the basis of the scientific method itself that helped the various steps of research between the theoretical framework and enable the fulfillment of the objectives and see the development of the same; I also have scientific, deductive, analytical techniques and instruments such as surveys also suggested method, the study population was 1 coach middle distance 16 athletes specialty one psychologist to specialty and we have the main results obtained in the number box 20 of which we get to meet the students there are coaches that they have much knowledge and dedication to the sport which it is found that there is a lack of pedagogical assessment test middle-distance athletes. Subsequently, based on the defined elements and proceeds to make the conclusions and recommendations in which the result of experience gained in the development of the research were discussed.